Prospective study of nonmyeloablative, HLA-mismatched unrelated BMT with high-dose posttransplantation cyclophosphamide - Yvette L. Kasamon; Richard F. Ambinder; Ephraim J. Fuchs; Marianna Zahurak; Gary L. Rosner; Javier Bolaños-Meade; Mark J. Levis; Douglas E. Gladstone; Carol Ann Huff; Lode J. Swinnen; William H. Matsui; Ivan Borrello; et al. (Blood Advances, 2017)
Abstract: Allogeneic blood or marrow transplantation (BMT) candidates may lack HLA-matched, related haploidentical, and unrelated umbilical cord options. Barriers to partially HLA-mismatched, unrelated donor (mMUD) BMT include excess graft-versus-host disease (GVHD), graft failure, and death. We prospectively studied nonmyeloablative (NMA) mMUD BMT with high-dose posttransplantation cyclophosphamide (PTCy) for patients with hematologic malignancies. Three transplants were performed with busulfan/fludarabine conditioning, with subsequent change to fludarabine/Cy/total body irradiation (flu/Cy/TBI). Twenty mMUD transplants are reported using flu/Cy/TBI, T-cell replete bone marrow grafts, and PTCy, mycophenolate mofetil, and sirolimus or tacrolimus (1 patient) for GVHD prophylaxis. The median patient age was 56. Of these unrelated grafts, 45% had ≥2 mismatched HLA loci, 25% had ≥3 mismatched loci, and 50% had HLA-C mismatches. No graft failure or grades 3-4 acute GVHD occurred. The median times to neutrophil recovery (≥500/µL) and platelet recovery (≥20 000/µL) were 19 days and 31 days, respectively. Full-donor chimerism was achieved in 95% of evaluable patients by day 60. The 180-day probability of grades 2-4 acute GVHD (all grade 2) was 25%, and the 1-year probability of any chronic GVHD was 16% (none severe). The 2-year nonrelapse mortality probability was 6%. With 4-year median follow-up, the 1-year progression-free and overall survival probabilities were 65% and 75%, respectively. NMA, T-cell replete mMUD BMT is thus a potentially viable option for patients without other suitable donors. This trial was registered at www.clinicaltrials.gov as #NCT01203722.